2007
DOI: 10.1111/j.1445-5994.2006.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for low‐grade gastric marginal zone lymphoma: a retrospective study

Abstract: Radiotherapy is an effective, well-tolerated treatment for patients with low-grade gastric marginal zone lymphoma, including those who have had prior therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Although RT is considered as a major risk factor for the development of secondary cancers, only 8% of secondary cancers are duo to RT and the remainders are due to genetic factors, lifestyle behaviors, and aging [25]. Some studies that followed patients for >7 years after RT to gastric MALToma reported variable secondary cancer incidence of 5-17%, as shown in Table 3 [5,8-10]. One study demonstrated that most of solid secondary cancers developed at sites distant from the irradiated area [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although RT is considered as a major risk factor for the development of secondary cancers, only 8% of secondary cancers are duo to RT and the remainders are due to genetic factors, lifestyle behaviors, and aging [25]. Some studies that followed patients for >7 years after RT to gastric MALToma reported variable secondary cancer incidence of 5-17%, as shown in Table 3 [5,8-10]. One study demonstrated that most of solid secondary cancers developed at sites distant from the irradiated area [8].…”
Section: Discussionmentioning
confidence: 99%